Financial crises and the dynamic linkages between stock and bond returns - Sercan Eraslan; Faek Menla Ali (Deutsche Bundesbank, 2017)
This paper investigates the dynamic linkages in terms of the first and second moments between stock and bond returns, within a wide range of advanced economies, over the different phases of the recent financial crisis. The adopted empirical framework is a bivariate volatility model, where volatility spillovers of either positive or negative sign are allowed for. Our results lend support to the existence of a substantial time-variation in the dynamic linkages between these financial assets over the different stages of the recent crisis. In particular, our results of the return spillovers show that such spillovers mostly run from stocks to bonds and exhibit a time-varying pattern over all three stages of the crisis in most countries. Regarding the volatility spillovers, such spillovers from bond returns to those of stocks are stronger than the other way round and also exhibit a time-varying pattern in most countries. Furthermore, the portfolio performance comparison results show that by considering time-varying return and volatility spillovers when calculating the risk-minimising portfolio weights of the selected assets, the portfolio volatility can be reduced despite limited diversification opportunities within national markets in times of financial crises.
Keywords: C32; C58; G15; 330; Bond prices; Financial crisis; Stock prices; Time-varying GARCH models; Volatility spillovers